Extern påverkan på intern revolutionär mobilisering - Scheding,Ben; Andersson,Christian (2026)
This study examines the extent to which American actors influenced domestic mobilization during the Orange Revolution in Ukraine between the years 2004 2005. This studies’ analysis focuses on how external support, from the United States, interacted with domestic political and social conditions during the revolution. Using qualitative methods, this study investigates the roles of US actors, like USAID and National Endowment for Democracy, in supporting domestic factors such as civil society, opposition groups and mobilization. The theory of the third wave of democratization, diffusion theory and social movement theory are combined as this studies’ theoretical framework. Findings show that support, through American actors, strengthened the organizational capacity of Ukrainian opposition movements. However, this study also concludes that external influence solely acted as reinforcing factors and thus not decisive. Furthermore, the underlaying factors for the revolution were widespread domestic dissatisfaction with corruption, electoral fraud and a government with authoritarian tendencies.
Keywords: Ukraina; Orangea revolutionen; USA; revolution; massmobilisering; demokratisering; postsovjetiskt; regeringskris; bilaterala relationer; bistånd